SOURCE: Sea Observations Utility for Reprocessing, Calibration and Evaluation - Oliveri, Paolo; Simoncelli, Simona; Di Pietro, Pierluigi; Fratianni, Claudia; Mattia, Gelsomina; Delrosso, Damiano; Guarnieri, Antonio (Frontiers in Marine Science, 2022)
SOURCE utility for reprocessing, calibration, and evaluation is a software designed for web applications that permits to calibrate and validate ocean models within a selected spatial domain using in-situ observations. Nowadays, in-situ observations can be freely accessed online through several marine data portals together with the metadata information about the data provenance and its quality. Metadata information and compliance with modern data standards allow the user to select and filter the data according to the level of quality required for the intended use and application. However, the available data sets might still contain anomalous data, bad data flagged as good, due to several reasons, i.e., the general quality assurance procedures adopted by the data infrastructure, the selected data type, the timeliness of delivery, etc. In order to provide accurate model skill scores, the SOURCE utility performs a secondary quality check, or re-processing, of observations through gross check tests and a recursive statistical quality control. This first and basic SOURCE implementation uses Near Real Time moored temperature and salinity observations distributed by the Copernicus Marine Environment and Monitoring Service (CMEMS) and two model products from Istituto Nazionale di Geofisica e Vulcanologia (INGV), the first an analysis and the second a reanalysis, distributed during CMEMS phase I for the Mediterranean Sea. The SOURCE tool is freely available to the scientific community through the ZENODO open access repository, consistent with the open science principles and for that it has been designed to be relocatable, to manage multiple model outputs, and different data types. Moreover, its observation reprocessing module provides the possibility to characterize temperature and salinity variability at each mooring site and continuously monitor the ocean state. Highest quality mooring time series at 90 sites and the corresponding model values have been obtained and used to compute model skill scores. The SOURCE output also includes mooring climatologies, trends, Probability Density Functions and averages at different time scales. Model skill scores and site statistics can be used to visually inspect both model and sensor performance in Near Real Time at the single site or at the basin scale. The SOURCE utility uptake allows the interested user to adapt it to its specific purpose or domain, including for example additional parameters and statistics for early warning applications.